2020
DOI: 10.1101/2020.11.11.378463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glutaric aciduria type 3 is a naturally occurring biochemical trait in inbred mice of 129 substrains

Abstract: The glutaric acidurias are a group of inborn errors of metabolism with different etiologies. Glutaric aciduria type 3 (GA3) is a biochemical phenotype with uncertain clinical relevance caused by a deficiency of succinyl-CoA:glutarate-CoA transferase (SUGCT). SUGCT catalyzes the succinyl-CoA-dependent conversion of glutaric acid into glutaryl-CoA preventing urinary loss of the organic acid. Here, we describe the presence of a GA3 trait in mice of 129 substrains due to SUGCT deficiency, which was identified by s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A recent study has demonstrated a decrease of metabolite concentrations in a GA1 mouse model with variants in the SUCGT (succinyl-CoA:glutarate-CoA transferase) gene, but this has not been studied in GA1 patients. 86 In contrast, elevated levels of 3-OH-GA (usually in combination with elevated concentrations of GA) are highly suggestive for GA1. Pitfalls for organic acid analysis should always be considered (Table S4).…”
Section: Confirmation Of a Positive Nbs Resultsmentioning
confidence: 99%
“…A recent study has demonstrated a decrease of metabolite concentrations in a GA1 mouse model with variants in the SUCGT (succinyl-CoA:glutarate-CoA transferase) gene, but this has not been studied in GA1 patients. 86 In contrast, elevated levels of 3-OH-GA (usually in combination with elevated concentrations of GA) are highly suggestive for GA1. Pitfalls for organic acid analysis should always be considered (Table S4).…”
Section: Confirmation Of a Positive Nbs Resultsmentioning
confidence: 99%